2020
DOI: 10.1111/ibi.12809
|View full text |Cite
|
Sign up to set email alerts
|

Testing alternative methods for estimation of bird migration phenology from GPS tracking data

Abstract: The development and miniaturization of GPS tracking devices has enabled a better understanding of migration phenology, but it can be challenging to identify where and when migration starts and ends, and researchers rely on multiple methods to infer it. Here, we use GPS tracks of 18 trans‐Saharan migrant White Storks Ciconia ciconia to determine how the choice of method influences the estimation of migratory timing and discuss its implications. We evaluate and provide R code for the implementation of five alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 28 publications
0
35
0
Order By: Relevance
“…The Bhote Koshi catchment, northeast of Kathmandu (red square in inset in Fig. 1), was also identified as one of the most affected areas, showing the greatest density of land-slides (Roback et al, 2018;Guo et al, 2017;Tanoli et al, 2017;Kargel et al, 2016;Collins and Jibson, 2015). The areal distribution of landslides away from the main shock epicentre appears to have been controlled by a combination of peak ground acceleration, slope, and fault rupture propagation (Roback et al, 2018;Martha et al, 2017;Regmi et al, 2016).…”
Section: Hazards and Their Interactions In The Area Of Studymentioning
confidence: 96%
See 2 more Smart Citations
“…The Bhote Koshi catchment, northeast of Kathmandu (red square in inset in Fig. 1), was also identified as one of the most affected areas, showing the greatest density of land-slides (Roback et al, 2018;Guo et al, 2017;Tanoli et al, 2017;Kargel et al, 2016;Collins and Jibson, 2015). The areal distribution of landslides away from the main shock epicentre appears to have been controlled by a combination of peak ground acceleration, slope, and fault rupture propagation (Roback et al, 2018;Martha et al, 2017;Regmi et al, 2016).…”
Section: Hazards and Their Interactions In The Area Of Studymentioning
confidence: 96%
“…Some authors pointed out that many coseismic landslides occurred at high elevations (e.g. Tanoli et al, 2017), and it was observed that after the earthquake, a large number of landslides remained disconnected from the channels, with significant amounts of material stored on the hillslopes (Cook et al, 2016;Collins and Jibson, 2015), including boulders that are still visible today on valley flanks. During the 2015 monsoon, new landslides were triggered along with the expansion of coseismic landslides, but loose material remained stored on the hillslopes by the end of the monsoon (Cook et al, 2016).…”
Section: Hazards and Their Interactions In The Area Of Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the importance of understanding migration phenology and common reporting of phenological information in movement-related wildlife analyses, a consistent methodology for determining departure and arrival dates has not yet emerged (Cerritelli et al, 2020; Soriano-Redondo et al, 2020). Often, there is no straightforward reproducible methodology, and authors provide vague descriptions of methods used to assign migration phenology to each individual (Shephard et al, 2015; Shimada et al, 2014).…”
Section: Example Applicationsmentioning
confidence: 99%
“…feeding behaviours among other things (e.g. Soriano-Redondo et al, 2020;Panicker et al, 2019;Gilbert et al, 2016). Whilst some trackers store the data internally and transmit it to a server via GSM when a network becomes available, the trackers used for this study have been developed to allow for a network of nodes that communicate wireless and in real time through an Internet of Things (IoT) system (e.g.…”
Section: Introductionmentioning
confidence: 99%